The relationship between the participatory budget and the budget execution of the District Municipality of Lurigancho for the year 2016 - Pacchua Guerra, William Adolfo (2021)
This article, entitled “The relationship between the Participatory Budget and the Budgetary Execution of the District Municipality of Lurigancho in 2016”, has as a general problem that drives the research of the article, the application of the following question: What is the relationship between the Participatory Budget with the Budgetary Execution of the District Municipality of Lurigancho, during the fiscal year 2016; likewise, the general objective is to determine to what extent the participatory budget is linked to the Budgetary Execution in the district of Lurigancho. The results were the high correlation existing between the participatory budget with the budget execution of the Municipality of Lurigancho, using Spearman’s RHO. Thus, this article is framed within the cross-sectional, correlational, descriptive, non-experimental and quantitative design. It is important to point out that a population of 36 people was used, made up of 28 agents involved in the participatory budget process and eight employees of the Municipality of Lurigancho, where the appropriate tools were used, prioritizing the questionnaire.